2013
DOI: 10.1136/thoraxjnl-2013-203728
|View full text |Cite
|
Sign up to set email alerts
|

Systemic tryptophan and kynurenine catabolite levels relate to severity of rhinovirus-induced asthma exacerbation: a prospective study with a parallel-group design

Abstract: Background Patients with allergic asthma have exacerbations which are frequently caused by rhinovirus infection. The antiviral tryptophan-catabolising enzyme indoleamine 2,3-dioxygenase (IDO) is induced by interferon-γ and suppressed by Th2 mediators interleukin (IL)-4 and IL-13. We hypothesised that local IDO activity after viral airway infection is lower in patients with allergic asthma than in healthy controls. Objective To determine whether IDO activity differs between patients with allergic asthma and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 37 publications
5
29
0
Order By: Relevance
“…It has been reported that systemic tryptophan and its catabolites relate to the severity of rhinovirus-induced asthma exacerbation in patients with allergic asthma [36]. In our study, a low level of l -tryptophan ( P14 ) was observed in the plasma of OVA-challenged mice, and this depletion of l -tryptophan ( P14 ) led to abnormalities of the energy metabolism.…”
Section: Resultssupporting
confidence: 48%
“…It has been reported that systemic tryptophan and its catabolites relate to the severity of rhinovirus-induced asthma exacerbation in patients with allergic asthma [36]. In our study, a low level of l -tryptophan ( P14 ) was observed in the plasma of OVA-challenged mice, and this depletion of l -tryptophan ( P14 ) led to abnormalities of the energy metabolism.…”
Section: Resultssupporting
confidence: 48%
“…Due to the systemic involvement, asthma exacerbation can also be monitored or even predicted by urinary metabolites including arachidonic derivatives such as leukotrienes (184,185) and urinary trypsin inhibitor (186). Exacerbated allergic asthma is accompanied with increased BAL levels of quinolinic acid, tryptophan, ECP, eosinophils (187), decreased CD29 (32) and CD44 (188) on eosinophils and elevated CD203c expression on basophils, which decreases significantly during remission (101 (189). While early or mild conditions are well-reflected local biomarkers, it appears that moderate to severe disease conditions are even visible in the peripheral blood.…”
Section: Biomarkers For Disease Severity and Exacerbationmentioning
confidence: 99%
“…The contribution of IDO in allergic airways disease in humans is an active area of study. In one study, IDO activity was significantly decreased in the BAL of patients with allergic asthma, providing a link between low IDO and airway hyperreactivity (19). …”
Section: Clinical Markers Of Allergic Tolerancementioning
confidence: 99%